Hubungan Persepsi Dan Latar Belakang Pendidikan Dengan Ketrampilan Praktikum Farmasetika Program Studi Diii Farmasi (The Correlation Of Perception And Educational Background To The Skills Of Pharmaceutical Practice In The Students Of Pharmacy Undergraduat - Nova Rahma Widyaningrum (Indonesian Journal on Medical Science, 2015)
Abstract: Perception of pharmaceutical practice is a prossess done by someone for interpretating the sensory impression they have, so that it will give a meaning for them. The students of pharmacy in Undergraduate Study Programm in Poltekkes Bhakti Mulia Sukoharjo have variances of educational background. Pharmaceutical practice is basic skills for the first level of study in pharmacy, that can improve and retread their capability being good technical personnel pharmacy. The differ of educational background will make any different in the way of their thinking, studying and also visioning. The purpose of this study was analyze the Correlation of Perception and educational background to the skills of pharmaceutical practice in the students of pharmacy undergraduate study programm in Poltekkes Bhakti Mulia Sukoharjo. This study was an quantitative research with cross sectional approach. The target population in the research was 82 students and the source population was 36 students. The sample was 36 students with the sampling technique was used by exhausting sample. The data analyze at the first hypothesis was analyzed using Spearman an Kendall’s tau correlation, the second one was analyzed using chi squere and coefficient contingency and the final one was analyzed using binary logistic regression. There was positively and tightly of correlation between perception to the skills of pharmaceutical practice at significance level = 0.000 and (p) value = 0.704; (r) = 0.666. There was positive and tight of correlation between educational background to the skills of pharmaceutical practice at pearson chi squere level = 22.377 > 7.815 and (C) value = 0.619. There was a positive significant correlation of Perception and educational background to the skills of pharmaceutical practice predicted by perception correlate value = 2.003 and educational background correlate value = 0.795. They contribute to the skills of pharmaceutical practice together as bis as 61.9 %.in conclusion, there was a positive significant correlation of Perception and educational background to the skills of pharmaceutical practice. Keywords: skills of pharmaceutical practice, educational background, perceptionAbstrak: Persepsi terhadap praktikum farmasetika merupakan suatu proses yang dilakukan individu untuk menginterpretasikan kesan inderawi sehingga akan memberikan makna bagi lingkungannya. Prodi DIII Farmasi Poltekkes Bhakti Mulia Sukoharjo memiliki mahasiswa yang bervariasi latar belakang pendidikannya. Praktikum Farmasetika merupakan ketrampilan dasar bagi mahasiswa farmasi untuk melatih mahasiswa menjadi tenaga teknis kefarmasian yang kompeten. Latar belakang pendidikan yang berbeda akan menimbulkan perbedaan pula pada cara pandang, cara berfikir dan cara belajar mahasiswa. Tujuan penelitian ini adalah menganalisis hubungan persepsi dan latar belakang pendidikan dengan ketrampilan praktik farmasetika pada mahasiswa Prodi DIII Farmasi di Poltekkes Bhakti Mulia Sukoharjo. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross sectional. Populasi sasaran dalam penelitian ini adalah 82 mahasiswa, sedang populasi sumber adalah 36. Sampel 36 mahasiswa dengan teknik pengambilan sampel menggunakan teknik exhausting sample. Analisis data pada uji hipotesa pertama dengan Analisa Korelasi Spearman dan Kendall‘s tau, dilanjutkan uji hipotesa kedua dengan chi squere dan coeffisient contingency, selanjutnya uji hipotesa ketiga dengan regresi logistik ganda. Ada hubungan positif dan erat antara persepsi dan ketrampilan praktikum farmasetika dengan nilai signifikansi 0.000 dan nilai (p) = 0.704; (r) = 0.666. Ada hubungan yang positif dan erat antara latar belakang pendidikan dengan ketrampilan praktik farmasetika dilihat dari nilai koefisien Pearson-Chi squere = 22.377 > 7.815 dan nilai (C) = 0.619. Ada hubungan yang positif antara persepsi dan latar belakang pendidikan dengan ketrampilan praktikum farmasetika dengan nilai koefisien persepsi sebesar 2.003 dan nilai koefisien latar belakang pendidikan sebesar 0.795, dengan kontribusi bersama sebesar 61.9 %. Simpulannya, terdapat hubungan positif yang signifikan antara persepsi dan latar belakang pendidikan dengan ketrampilan praktikum farmasetika. Kata kunci: ketrampilan praktikum farmasetika, latar belakang pendidikan, persepsi.